Simulation tools for mobile ad-hoc sensor networks: A state-of-the-art survey - Mohamad Nazim, Jambli; Halikul, Lenando; Kartinah, Zen; Sinarwati, Mohamad Suhaili; Alan, Tully (IEEE, 2013)
Mobile ad-hoc sensor networks (MASNETs) have recently become an important area of research for Mobile adhoc networks (MANETs) researchers. The increasing capabilities and the decreasing costs of sensors make MASNETs applications possible to be deployed in real world. However, before such application can be deployed, their performance need to be measured first. But, the use of real-world measurement is costly and time consuming. Therefore, it is more economical and practical to use simulation tools to simulate MASNETs applications. Although, there are many existing simulation tools for MANETs, most of them are not suitable for MASNETs due to resource-constraint of such networks. Therefore, it is essential to have a survey of the existing simulation tools for MASNETs. In this paper, the comparative study on different simulation tools is conducted to identify the most appropriate tool for MASNETs